2015
DOI: 10.1158/1940-6207.capr-14-0306
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant TET1 Methylation Closely Associated with CpG Island Methylator Phenotype in Colorectal Cancer

Abstract: Inactivation of methylcytosine dioxygenase, ten-eleven translocation (TET) is known to be associated with aberrant DNA methylation in cancers. Tumors with a CpG island methylator phenotype (CIMP), a distinct subgroup with extensive DNA methylation, show characteristic features in the case of colorectal cancer. The relationship between TET inactivation and CIMP in colorectal cancers is not well understood. The expression level of TET family genes was compared between CIMP-positive (CIMP-P) and CIMP-negative (CI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
(50 reference statements)
4
35
0
1
Order By: Relevance
“…We found that CRCs in the CIMP-high category showed significantly lower levels of TET1 expression than CIMP-low or CIMP-negative tumors (Fig 1A), which is consistent with previous observations [18]. We next carried out RT-qPCR with TET1 in a series of CRC cell lines, and found that the majority of CRC lines (8 of 12) expressed lower levels of TET1 than normal colonic tissues, whereas two lines (Colo320DM and CaCO2) showed upregulated TET1 expression (Fig 1B).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…We found that CRCs in the CIMP-high category showed significantly lower levels of TET1 expression than CIMP-low or CIMP-negative tumors (Fig 1A), which is consistent with previous observations [18]. We next carried out RT-qPCR with TET1 in a series of CRC cell lines, and found that the majority of CRC lines (8 of 12) expressed lower levels of TET1 than normal colonic tissues, whereas two lines (Colo320DM and CaCO2) showed upregulated TET1 expression (Fig 1B).…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, we and others recently reported that TET1 is silenced in association with promoter CpG island hypermethylation in a subset of CRC cell lines [18]. TET1 methylation is preferentially observed in CIMP-positive primary CRCs as well as in CIMP-positive colorectal adenomas [18]. Methylation of TET1 CpG island in primary CRC is also reported by another group recently [19].…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Although TETs mutation in CRC is rarely studied, alteration of their methylation is frequently addressed. Norihisa Ichimura et al demonstrated TET1 methylation could contribute to CRC, thus aiding in CRC diagnosis [78]. Another study confirmed TET1 was involved in cancer cells proliferation via WNT signal pathway.…”
Section: Demethylation Via 5hmc Conversion In Cancermentioning
confidence: 99%